2020
DOI: 10.2196/preprints.21757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Web-Based Group Mindfulness Training on Stress and Sleep Quality in Singapore During the COVID-19 Pandemic: Retrospective Equivalence Analysis (Preprint)

Abstract: BACKGROUND The COVID-19 pandemic has had a negative impact on psychological health. Mindfulness training, which helps individuals attend to the present moment with a non-judgmental attitude, improves sleep and reduces stress in regular times, and may be relevant in mitigating harmful health consequences during acute crises. However, restrictions may necessitate this training being delivered online, rather than in in-person group settings. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Mindfulness training was proven to be effective in improving well-being and reducing perceived stress in several populations (especially those prone to burnout) and conditions [8][9][10] . These effects were also found in online training, in particular during Covid-19 lockdowns by some preliminary results 33,62 . The aim of this study was to test the effectiveness of online mindfulness training after the first Italian Covid-19 lockdown, when the measures to prevent contagion were loosened, but the second wave was starting to emerge.…”
Section: Principal Results and Comparison With Prior Workmentioning
confidence: 56%
See 1 more Smart Citation
“…Mindfulness training was proven to be effective in improving well-being and reducing perceived stress in several populations (especially those prone to burnout) and conditions [8][9][10] . These effects were also found in online training, in particular during Covid-19 lockdowns by some preliminary results 33,62 . The aim of this study was to test the effectiveness of online mindfulness training after the first Italian Covid-19 lockdown, when the measures to prevent contagion were loosened, but the second wave was starting to emerge.…”
Section: Principal Results and Comparison With Prior Workmentioning
confidence: 56%
“…As a matter of fact, several studies assessing the efficacy of online mindfulness-based interventions during lockdown are emerging. An online mindfulness training significantly reduced perceived stress in Singaporean participants during lockdown 33 . The same study found comparable effects for online and in-person mindfulness training.…”
Section: Online Mindfulness Training and Covid-19 Pandemicmentioning
confidence: 92%
“…Mindfulness training programs were proven to be effective in improving well-being and reducing perceived stress in several populations (especially those prone to burnout) and conditions 8-10 . These effects were also found in online training, in particular during Covid-19 lockdowns by some preliminary results 40,51 . The aim of this study was to test the effectiveness of an online mindfulness training program after the rst Italian Covid-19 lockdown, when the measures to prevent contagion were loosened, but the second wave was starting to emerge.…”
Section: Discussionmentioning
confidence: 56%
“…As a matter of fact, several studies assessing the e cacy of online mindfulness-based interventions during lockdown are emerging. An online mindfulness intervention signi cantly reduced perceived stress in Singaporean participants during lockdown 40 . The same study found comparable effects for online and in-person mindfulness training programs.…”
Section: Online Mindfulness Training Programs and Covid-19 Pandemicmentioning
confidence: 99%